A STEM-Oriented Digital Mentoring Approach to Enhance Teachers’ Digital Literacy in Primary Education - Suci Siti Lathifah; Nurlinda Safitri; Ratih Purnamasari; Reni Marlina (FKIP UNIVERSITAS PAKUAN, 2025)
This study aims to analyse the effectiveness of STEM (Science, Technology, Engineering, and Mathematics) mentoring based on digital technology in enhancing the digital literacy of teachers, in response to the demands of 21st-century learning. Employing a mixed-methods action research design, the study involved four stages: planning, action, observation, and reflection. The participants consisted of 15 teachers from a Public Elementary School in Bogor, selected through purposive sampling. The mentoring programme included training in digital device usage, the development of STEM-based learning media, and the implementation of technology-driven projects. The findings demonstrate a significant improvement in the digital literacy of primary school teachers. Prior to the programme, the average digital literacy score was 58 (low category), which increased to 82 after the programme, confirming its effectiveness. The study highlights the potential of an integrated STEM and digital technology approach to improve teacher competencies. It also underlines the importance of continuous support through learning communities and access to digital resources to ensure the sustainability of professional development. Enhancing teachers’ digital literacy is key to fostering innovative and relevant pedagogical strategies that align with the digital era. This research recommends broader application of similar mentoring models to improve the quality of basic education in Indonesia.